The sacred thread : Hinduism in its continuity and diversity - Brockington, J. L. (Edinburgh University Press, 1996)
This classic introduction to Hinduism, now updated and including 14 illustrations of the Hindu deities, takes the Western reader through the concepts of the Hindu faith, from its Vedic origins to its present development.